A Behavioral Confirmation and Reduction of the Natural versus Synthetic Drug Bias. (May 2019) - Meier, Brian P.; Dillard, Amanda J.; Osorio, Eric; Lappas, Courtney M.
Research reveals a biased preference for natural v. synthetic drugs; however, this research is based on self-report and has not examined ways to reduce the bias. We examined these issues in 5 studies involving 1125 participants. In a pilot study ( N = 110), participants rated the term natural to be more positive than the term synthetic, which reveals a default natural-is-better belief. In studies 1 ( N = 109) and 2 ( N = 100), after a supposed personality study, participants were offered a thank you "gift" of a natural or synthetic pain reliever. Approximately 86% (study 1) and 93% (study 2) of participants chose the natural v. synthetic pain reliever, which provides a behavioral choice confirmation of the natural drug bias. In studies 3 ( N = 350) and 4 ( N = 356), participants were randomly assigned to a control or experimental condition and were asked to consider a scenario in which they had a medical issue requiring a natural v. synthetic drug. The experimental condition included a stronger (study 3) or weaker (study 4) rational appeal about the natural drug bias and a statement suggesting that natural and synthetic drugs can be good or bad depending on the context. In both studies, the natural bias was reduced in the experimental condition, and perceived safety and effectiveness mediated this effect. Overall, these data indicate a bias for natural over synthetic drugs in preferences and behavioral choices, which might be reduced with a rational appeal.